Effects of Light-Burnt Dolomite Incorporation on the Setting, Strength, and Drying Shrinkage of One-Part Alkali-Activated Slag Cement - Jeon, In Kyu; Ryou, Jae Suk; Jakhrani, Sadam Hussain; Kim, Hong Gi (Materials, 2019)
This study investigates the potential of light-burnt dolomite (LBD) as a supplementary cementitious material with ground granulated blast furnace slag (GGBFS) and Ordinary Portland cement (OPC). In this work, LBD was substituted for up to 20% of GGBFS in sodium sulfate-activated slag systems. The effects of LBD incorporation on the flow, setting time, compressive and flexural strength development, and drying shrinkage were explored with, X-ray diffraction and thermogravimetric analyses. LBD incorporation resulted in greater strength development of an alkali-activated slag system. The optimum LBD content for strength development was 10%, regardless of ordinary Portland cement content. In addition, LBD decreased the drying shrinkage, accelerated the hydration process, and induced hydrotalcite formation, which can be attributed to the reactive MgO inside LBD.